Bimbingan Teknis Pengembangan Tanaman Pisang Berbasis Pupuk Organik di Kampung Kweel Distrik Elikobel Papua Selatan - Diana Sri Susanti; Yosehi Mekiuw; Mani Yusuf; Wa Ode Asryanti Wida Malesi; Anwar Anwar; Maya Sari Rupang (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Banana is a horticultural commodity that is widely consumed by people in Indonesia, especially in Merauke Regency. Increased production of banana plants is strongly influenced by the quality of seeds and preparation of planting media in the field. This service aims to provide an understanding to the community about the development of banana plants using organic fertilizers and utilizing the potential of unused land in Kweel Village. The implementation of activities includes counseling with a participatory system and demonstration of banana plant development plots. The solutions offered in this activity are; 1) Providing counseling about the benefits of managing livestock waste as organic fertilizer, 2) Providing assistance in processing livestock manure as organic fertilizer and 3) conducting technical guidance and demonstration of banana plant development plots. The targeted outputs of this Partner Village Development program include guidelines for the use of organic fertilizers for banana cultivation, publication of articles in nationally accredited journals, and publication of print/online media.